2006
DOI: 10.2135/cropsci2005.0126
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Irrigated Tall Fescue–Legume Communities under Two Grazing Frequencies in the Southern Rocky Mountains, USA

Abstract: Irrigated pastures form a significant component of agriculture in the irrigated steppe of the southern Rocky Mountains, USA. Information is limited, however, describing performance of grazed binary perennial cool-season grass-legume mixtures in the region. Established monoculture tall fescue [Festuca arundinacea Schreb. 5 Lolium arundinaceum (Schreb.) S.J. Darbyshire] 1 134 kg N ha 21 (MONO) and tall fescue mixed with alfalfa (Medicago sativa L.) (ALF/TF), birdsfoot trefoil (Lotus corniculatus L.) (BFT/TF), ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Trampling also may not have been a problem for the turnip and, possibly, the oat because most of the turnip stand established on the sides of the beds where trampling would be less likely as has been reported in other research [16,17]. Although not compared in the present study, cattle also will select the higher quality plant species first in mixed pastures [40] (e.g., turnip vs. maize in the maize-turnip treatment, Table 2). …”
Section: Post-grazing Overseeded Forage Biomass and % Disappearancementioning
confidence: 56%
“…Trampling also may not have been a problem for the turnip and, possibly, the oat because most of the turnip stand established on the sides of the beds where trampling would be less likely as has been reported in other research [16,17]. Although not compared in the present study, cattle also will select the higher quality plant species first in mixed pastures [40] (e.g., turnip vs. maize in the maize-turnip treatment, Table 2). …”
Section: Post-grazing Overseeded Forage Biomass and % Disappearancementioning
confidence: 56%
“…In addition to the production benefits of forage legumes, their forage nutritive value is important. This potential for yield compensation by legumes can be instrumental in improving the seasonal distribution of forage and increasing the capacity of a pasture to support livestock grazing throughout the summer (Leep et al, 2002;Lauriault et al, 2006). Multiple studies have shown that grass-legume mixtures improve crude protein (CP) and neutral detergent fiber (NDF) content in forage compared with the grass monocultures (Malhi et al, 2002;Zemenchik et al, 2002;Kopp et al, 2003;Deak et al, 2007;Kleen et al, 2011) Forage legumes commonly used in grass-legume mixtures, such as alfalfa (Medicago sativa L.) (ALF) and birdsfoot trefoil (Lotus corniculatus L.) (BFTF), are productive during summer months when cool-season grass production is low.…”
mentioning
confidence: 99%
“…Legume intake is typically higher than grasses due to lower cell wall content, higher crude protein, and faster rate of particle size reduction and passage rate of the rumen (Rook and Yarrow, 2002;Elgersma and Søegaard, 2016). Furthermore, the ability of ALF to increase production of grasses when grown together can be similar to that of commercial N fertilizer (Guldan et al, 2000;Sleugh et al, 2000;Berdahl et al, 2001;Lauriault et al, 2006). This potential for yield compensation by legumes can be instrumental in improving the seasonal distribution of forage and increasing the capacity of a pasture to support livestock grazing throughout the summer (Leep et al, 2002;Lauriault et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations